Efisiensi Daya Sel Surya Menggunakan Konverter DC-DC Mensuplai Beban Listrik - Parlindungan Pandapotan Marpaung (Yayasan Literasi Sains Indonesia, 2023)
The maximum solar cell power capacity without load parameter Pm(no-load) = 0.4 watts is used to supply an external electrical load with a resistor R in ohms. Irradiation of the solar cell surface area during the day in bright sunlight supplies an electrical load with a resistor R = 100 Ω which absorbs solar cell power with parameters Psel(R) = 0.09 watts. The power efficiency of a solar cell loaded with a resistor R is expressed as the parameter eff.sel(R) which is the result of a comparison between the power Psel(R) = 0.09 watts and the power Pm(no-load) resulting in a value of eff.sel(R) = 22.5% . Achieving solar cell to more effectively supply a resistor load of R = 100 Ω is efficiency done by adding a parallel FC-75 type dc-dc buck converter device to the solar cell output. Test results: The input power of the FC-75 dc-dc buck converter is Pi(conv.) = 0.178 watts. The resistor load R absorbs the output power Po[conv.(R)] = 0.078 watts. The power efficiency of solar cells using a dc-dc buck converter is expressed as the eff.sel(conv.) parameter. The results of the comparison between the power Po[conv.(R)] and the power Pi(conv.) reach 43.82%. The achieved power efficiency results for solar cells supplying resistor load R using a dc-dc buck converter are eff.sel(conv.) = 43.82%, which is greater than eff.sel(R) = 22.5%.